LETHAL TIME BIOLARVA PADA LARVA AEDES AEGYPTI - Firda Yanuar Pradani; I Gede Wempi Dody Surya Permadi (POLTEKKES KEMENKES JAYAPURA, 2021)
Aedes aegypti is a Dengue Hemorrhagic Fever (DHF) vector caused by mosquitoes bites from DHF patients to healthy humans. Aedes aegypti needs an optimized temperature to continue their generation. At the larval stage, the temperature required by the larva is 37 Â° C with a pH of 7. At optimal temperature, the larvae can become adult mosquitoes that harm humans. Larval control through chemical insecticides can pollute the environment so that natural insecticides are needed. This study aims to identify LT50 biolarvacide 2% concentration. This study is carried out through a systematic review. Of the 125 articles, nine were selected, which were used as the main library. The nine articles use biological larvicides to control Aedes larvae aegypti with lethal time (LT50) varies from 1 hour to 24 hours. Legundi leaves in a concentration of 2% have the fastest LT50, which is 1 hour, while zodia has the longest lethal time of 24 hours with the same attention.